2011
DOI: 10.1152/ajpendo.00061.2011
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol, an isoprenoid, improves metabolic abnormalities in mice via both PPARα-dependent and -independent pathways

Abstract: Peroxisome proliferator-activated receptors (PPARs) control energy homeostasis. In this study, we showed that farnesol, a naturally occurring ligand of PPARs, could ameliorate metabolic diseases. Obese KK-Ay mice fed a high-fat diet (HFD) containing 0.5% farnesol showed significantly decreased serum glucose level, glucosuria incidence, and hepatic triglyceride contents. Farnesol-containing HFD upregulated the mRNA expressions of PPARα target genes involved in fatty acid oxidation in the liver. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 62 publications
0
39
2
1
Order By: Relevance
“…The CAR-target gene CYP2B was also induced, although more strongly in rat than in mouse hepatocytes. Although CAR is suggested to influence hepatocellular lipid metabolism (Dong et al, 2009;Goto et al, 2011a), the panel of fatty acid-metabolizing enzymes altered by isoprenoids in this study did not appear to be strongly regulated through CAR activation.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The CAR-target gene CYP2B was also induced, although more strongly in rat than in mouse hepatocytes. Although CAR is suggested to influence hepatocellular lipid metabolism (Dong et al, 2009;Goto et al, 2011a), the panel of fatty acid-metabolizing enzymes altered by isoprenoids in this study did not appear to be strongly regulated through CAR activation.…”
Section: Discussioncontrasting
confidence: 68%
“…†Statistically significant compared with DMSOtreated hepatocytes (P , 0.05). Takahashi et al, 2002;Goto et al, 2011a), which is suggested to partially account for some of these effects (Goto et al, 2011a). In the current study, many of the orthologs uniquely affected by SQ1 treatment were associated with fatty acid metabolism and are also transcriptional targets of PPARa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonsterol Isoprenoids Activate hCAR1 599 at ASPET Journals on May 12, 2018 dmd.aspetjournals.org Downloaded from Takahashi et al, 2002;Goto et al, 2011a). We previously reported that accumulation of isoprenoids in response to squalene synthase inhibition increased CYP2B1 expression in primary rat hepatocytes in a CAR-dependent manner (Kocarek et al, 1998;Kocarek and MercerHaines, 2002).…”
Section: Discussionmentioning
confidence: 98%